2019
DOI: 10.1093/treephys/tpz046
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles enter the tree stem faster through leaves than through roots

Abstract: A major environmental pollution problem is the release into the atmosphere of particulate matter, including nanoparticles (NPs), which causes serious hazards to human and ecosystem health, particularly in urban areas. However, knowledge about the uptake, translocation and accumulation of NPs in plant tissues is almost completely lacking. The uptake of silver nanoparticles (Ag-NPs) and their transport and accumulation in the leaves, stems and roots of three different tree species, downy oak (Quercus pubescens W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 77 publications
5
25
0
Order By: Relevance
“…The median for roots was 127.3% (geometric mean = 140.4%) whereas for foliage was 114.9% (geometric mean = 126.7%), and the two distributions differed significantly (Kruskal-Wallis, H = 11.79, P < 0.001). While nanoparticles may enter the tree stem faster when applied to leaves than when applied to roots (Cocozza et al, 2019), this analysis revealed that applying nanoparticles onto leaves does not necessarily yield higher MAX. Further, the root entries were grouped into two categories: a) those with plants grown in a liquid growing medium (hydroponic system, n = 88) and b) those with plants grown in soil substrate (no hydroponic system, n = 179).…”
Section: Discussionmentioning
confidence: 86%
“…The median for roots was 127.3% (geometric mean = 140.4%) whereas for foliage was 114.9% (geometric mean = 126.7%), and the two distributions differed significantly (Kruskal-Wallis, H = 11.79, P < 0.001). While nanoparticles may enter the tree stem faster when applied to leaves than when applied to roots (Cocozza et al, 2019), this analysis revealed that applying nanoparticles onto leaves does not necessarily yield higher MAX. Further, the root entries were grouped into two categories: a) those with plants grown in a liquid growing medium (hydroponic system, n = 88) and b) those with plants grown in soil substrate (no hydroponic system, n = 179).…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, NPs may undergo different transformations after their accumulation in roots, followed by their translocation to above-ground organs as it has been observed for selenium nanoparticles (Se NPs) and AgNPs in garlic and Arabidopsis plants, respectively [ 13 , 14 ]. Finally, it is worth mentioning the accumulation of AgNPs in stems of three different tree species was faster after foliar treatment compared to roots treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant changes in physiological data, such as net the photosynthetic rates, growth, leaf temperature, or plugging of stomata, were observed after the trees had been exposed to BC particles [16]. On the other hand, Cocozza et al [17] indicated that the foliar application of Ag-nanoparticles decreased the growth, aboveground biomass, and stem length in poplar, but not in oak and pine. These differences of results among tree species may be caused by the variation of the surface structures of leaves and needles.…”
Section: Introductionmentioning
confidence: 99%